2008
DOI: 10.1029/2007tc002216
|View full text |Cite
|
Sign up to set email alerts
|

Seismic reflection evidence for a Dangerous Grounds miniplate: No extrusion origin for the South China Sea

Abstract: The collision of India and Asia has caused large strike‐slip faults to form in east Asia, resulting in the “extrusion” of crustal blocks toward the southeast since the Eocene as a result of the indentation of rigid India into Asia. It has been suggested that the South China Sea opened as a result of relative motion between a rigid Indochina (Sundaland) block and China. Alternative models propose that rifting and seafloor spreading were driven by trench forces to the south. We test these competing models by ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(135 citation statements)
references
References 91 publications
3
128
1
1
Order By: Relevance
“…1b for locations). In addition, we incorporated published stratigraphic schemes from the study area (Hinz and Schlueter 1985;Hinz et al 1989;Clift et al 2008;Franke et al 2008Franke et al , 2013Cullen et al 2010;Hutchison and Vijayan 2010;Yao et al 2012;Ding et al 2011). In the Fig.…”
Section: Datasets and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b for locations). In addition, we incorporated published stratigraphic schemes from the study area (Hinz and Schlueter 1985;Hinz et al 1989;Clift et al 2008;Franke et al 2008Franke et al , 2013Cullen et al 2010;Hutchison and Vijayan 2010;Yao et al 2012;Ding et al 2011). In the Fig.…”
Section: Datasets and Methodsmentioning
confidence: 99%
“…The initial subsidence during the active extensional phase has been recognized from the late Cretaceous (Tg, *65 Ma) to the late Oligocene (T70, *32 Ma). Previous studies have suggested episodic extension in the continental margin of the South China Sea with combined influences of the eastward retreat of the West Pacific subduction zone and the collision and northward impinging of the India Block to the Tibet Block (Tapponier et al 1986;Zhou et al 1995;Clift et al 2008;Cullen et al 2010). In our study, a classification of extensional episodes has not been carried out and the tectonic subsidence during this stage has been simplified.…”
Section: Cenozoic Tectonic Subsidencementioning
confidence: 99%
“…In the continental margins of the SWSB, a highly attenuated crust and an ultra-wide rift half graben/half host structure was the result of progressive stretching with additional regional extension events occurring along different segments of the rift grabens and basins from the late Eocene to the middle Oligocene . After the Dangerous Grounds had collided with Borneo in the middle Miocene (Hutchison 2004;Clift et al 2008;Cullen et al 2010;Hutchison and Vijayan 2010), the stress dominant setting of the southern margin changed into a compression. There are several basement high features around the SWSB, including the Macclesfield Bank, Reed Bank, Zhongjian Massif and Zhenghe Massif.…”
Section: Geological Settingmentioning
confidence: 99%
“…Furthermore, rifting was terminated during active propagation as result of the collision of the southern Dangerous Grounds margin with Borneo (Hutchison et al 2000;Clift et al 2008;Hinz et al 1989). This basin was formed as a result of extension starting in the Late Cretaceous and accelerating during the Eocene, culminating in breakup and the onset of seafloor spreading likely around 30 Ma, at least offshore of southern China (Su et al 1989;Briais et al 1993;Ru and Pigott 1986;Franke et al 2014;Barckhausen et al 2014).…”
Section: South China Seamentioning
confidence: 99%